(untitled) (Sinología hispánica. China Studies Review, 2020)
The present study aims at comparing the move structures of Chinese and American negative online shopping reviews and managerial responses, and the influence of negative online reviews on peer customer. The researchers collected 158 Chinese negative shopping reviews from www.jd.com, followed by 157 managerial responses and 76 peer customer responses, and 156 American negative reviews from www.amazon.com, followed by 139 managerial responses and 97 peer customer responses, respectively. The negative online reviews were analyzed into explicitly-impolite and implicit-impolite moves, the managerial responses were analyzed into rapport-enhancing and rapport-damaging move, and the peer customer responses were analyzed into agreement and disagreement with the negative online reviews. After qualitative analysis, the researchers conducted chi-square to examine whether the differences between the Chinese and American negative online reviews and managerial and peer customer responses were significant of not. The results show that the American negative online reviewer has matured as a genre, in that American negative online reviewers not only criticized the commodity, service, etc., but also warned other customers against making the purchase, while Chinese negative online reviews mainly aimed at criticizing the commodity, services, etc., leaving the decision to the peer customer. In terms of managerial responses, the Chinese manufacturer responded significantly more to the negative online reviewer, but employed more rapport-damaging moves than their American counterpart. By contrast, the American manufacturer customized their greeting and rectification with a unique reference code, which make their managerial responses more individualized. As for peer-customer responses, the results show that negative online reviews had a greater impact on Chinese peer customers than their American equivalents. The findings may provide directions for the Chinese and American negative reviewers and the management to adjust their move structures of negative reviews and managerial responses to the negative online shopping reviews according to target consumers.